Comparative study of different surgical approaches for treatment of UPJ obstruction according to the degree/severity of hydronephrosis factor - Zhao, Peng; Wang, Cao; Mao, Kaiyi; Luo, Zhen; Li, Yingbo; Zhou, Guangxu; Tan, Hongyang; Liu, Hong; Mao, Yucheng; Ma, Hong; Shang, Xianhui; Liu, Bin (Frontiers in Pediatrics, 2022)
Objective To compare the efficacy of two different surgical approaches during and after pyeloplasty according to the degree/severity of hydronephrosis factor. Materials and Methods 60 child patients with UPJ obstruction admitted to our hospital from August 2019 to October 2021 were collected. Patients who underwent retroperitoneal laparoscopic pyeloplasty (RPLP) were enrolled into Group A (n = 20), while those who received transperitoneal laparoscopic pyeloplasty (TLP) were selected as Group B (n = 40). Clinical parameters, including gender, age, laterality of UPJ obstruction,degree/severity of hydronephrosis, body weight, operation time, drainage tube indwelling time, complete oral feeding time, and length of hospital stay, were compared between the two groups. Results All 60 child patients were operated upon successfully without conversion to open surgery. There were no statistically significant differences in gender, age, laterality of UPJ obstruction, and body weight between the two groups, while the operation time of TLP was shorter than that of RPLP, indicating a statistically significant difference (P < 0.001). The differences in complete oral feeding time, drainage tube indwelling time, and length of hospital stay were statistically significant between the two groups, and RPLP was superior to TLP in terms of postoperative recovery time (P < 0.001). A stratified comparison showed that there were no statistically significant differences in anteroposterior diameter ≤ 20 mm, while there were statistically significant differences in anteroposterior diameter > 20 mm. Hydronephrosis is reviewed after 3 months of the opration, degree/severity of hydronephrosis have been reduced。 Conclusion Both RPLP and TLP are safe and feasible in the treatment of UPJ obstruction, and their overall surgical effects are equivalent. For child patients with anteroposterior diameter ≤ 20 mm, RPLP is available, while patients with anteroposterior diameter > 20 mm, TLP is recommended.